Why should we correct reported pulsation frequencies for stellar line-of-sight Doppler velocity shifts?. (28th September 2014) - Davies, G. R.; Handberg, R.; Miglio, A.; Campante, T. L.; Chaplin, W. J.; Elsworth, Y.
Abstract : In the age of Kepler and CoRoT, extended observations have provided estimates of stellar pulsation frequencies that have achieved new levels of precision, regularly exceeding fractional levels of a few parts in 10 4 . These high levels of precision now in principle exceed the point where one can ignore the Doppler shift of pulsation frequencies caused by the motion of a star relative to the observer. We present a correction for these Doppler shifts and use previously published pulsation frequencies to demonstrate the significance of the effect. We suggest that reported pulsation frequencies should be routinely corrected for stellar line-of-sight velocity Doppler shifts, or if a line-of-sight velocity estimate is not available, the frame of reference in which the frequencies are reported should be clearly stated.